2013
DOI: 10.1371/journal.pone.0075953
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Chromosomal Abnormalities in Early Spontaneous Abortion after Assisted Reproductive Technology: A Meta-Analysis

Abstract: BackgroundStudies on the risk of chromosomal abnormalities in early spontaneous abortion after assisted reproductive technology (ART) are relatively controversial and insufficient. Thus, to obtain a more precise evaluation of the risk of embryonic chromosomal abnormalities in first-trimester miscarriage after ART, we performed a meta-analysis of all available case–control studies relating to the cytogenetic analysis of chromosomal abnormalities in first-trimester miscarriage after ART.MethodsLiterature search … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 30 publications
0
14
0
1
Order By: Relevance
“…Yet in humans, studies are scarce and less conclusive. In this context when comparing natural and stimulated cycles, no differences have been observed in terms of cleavage capacity [3], oocyte [4], and embryo aneuploidy rate [5], or incidence of aneuploidy in either aborted foetuses [6] or chorionic villus sampling late in the first trimester of pregnancy [7]. …”
Section: Introductionmentioning
confidence: 99%
“…Yet in humans, studies are scarce and less conclusive. In this context when comparing natural and stimulated cycles, no differences have been observed in terms of cleavage capacity [3], oocyte [4], and embryo aneuploidy rate [5], or incidence of aneuploidy in either aborted foetuses [6] or chorionic villus sampling late in the first trimester of pregnancy [7]. …”
Section: Introductionmentioning
confidence: 99%
“…And for women with recurrent miscarriages of chromosome anomaly, we could provide further pre-implantation genetic diagnosis in the following conceptions. Although the history of receiving ART (assisted reproductive technology) not being documented in our study, Qin et al reviewed 1896 cases and declared that ART treatment wouldn't increase the risk for chromosomal abnormalities in the first trimester miscarriages [11].…”
Section: Discussionmentioning
confidence: 67%
“…The abnormality rate is 53.0% (95% CI 44.8–61.3%), which is similar to that observed in spontaneous miscarriage (49.7%). In a meta‐analysis carried out by Qin et al, it was found that the frequency of chromosomal abnormality in early spontaneous miscarriages after ART was not significantly increased compared with those in natural conceptions. In addition, the frequency of chromosomal abnormality in early spontaneous miscarriages following in vitro fertilisation (IVF) was similar to those observed following ICSI.…”
Section: Resultsmentioning
confidence: 99%
“…Nowadays, multi-fluor FISH, in which each chromosome appears to be painted with a different colour, can quickly scan a set of chromosomes with limited resolution. In practice it is unusual to use the complete set of 24 probes; instead, between five and seven probes are selected for the chromosomes most commonly involved in aneuploidy (for example 13,14,15,16,18,21,22, and X). The resolution of FISH is 40-250 kb per probe for a single site.…”
Section: Fluorescence In Situ Hybridisationmentioning
confidence: 99%